Investigation of Application Niche for Sustainable Wastewater Treatment Using Microbial Fuel Cells - (:unkn) unknown (My University, 2013)
Microbial fuel cells represent a sustainable wastewater treatment technology due to its simultaneous treatment of contaminants and electricity production. Selection of suitable substrates is important to identifying proper application of microbial fuel cell (MFC) technology. In this work, four identical MFCs were used to treat the wastes sampled from different stages of a cheese wastewater treatment process, and both treatment performance and energy balance were examined. The two MFCs treating liquid wastes achieved more than 80% removal of total chemical oxygen demand (TCOD), while the other two MFCs fed with sludge or cheese whey removed about 60% of TCOD. The suspended solids were greatly reduced in all MFCs. Nutrient removal mainly occurred with nitrite and ammonia reduction, while the phosphate decrease was insignificant. The MFC-2 treating the DAF (dissolved air flotation) effluent generated the highest Coulombic efficiency of 27.2±3.6 % and the highest power density of 3.2±0.3 W/m3. Because of the low contaminant concentrations in the DAF effluent, the MFC-2 consumed the least amount of energy of 0.11 kWh/m3. None of the tested MFCs achieved an energy-neutral balance, mainly because of the small connecting ports (which resulted in high recirculation energy) and the use of cathode aeration. Our results suggest that MFCs may be more suitable for treating low-strength wastewater in terms of both treatment and energy performance. Owing to the importance of nutrient (nitrogen and phosphorus) control in wastewater treatment operations, this work also reviews the removal and recovery of nutrients in various bioelectrochemical systems (BES) including microbial fuel cells and microbial electrolysis cells, discusses the influence factors and potential problems, and identifies the key challenges for nitrogen and phosphorus removal/recovery in a BES.
Keywords: Bioelectrochemical Systems; Microbial Fuel Cells; Nutrient Removal and Recovery; Wastewater Treatment